Tomato Jos: launching a tomato paste brand in Nigeria. Issue 1 (12th January 2022) - Maritz, Jaco; Peters, Mark
Abstract : Learning outcomes: The teaching objectives of the case are as follows: to develop an understanding of the scope and complexity of strategy and marketing; to examine what is meant by purpose, direction, objectives and consider how these might be set and used; to help students think and act in a strategic way; to give faculty the opportunity to illustrate the strategist's and marketer's toolbox, namely, tools and frameworks, such as Porters 5 Forces – The attractiveness of the industry, Porter's Generic Marketing Strategies, strengths, weaknesses, opportunities, threats analysis, the 4P's – with a focus on product and distribution. The case is intended for use in MBA and Executive education courses in strategy, marketing and leadership. The case offers relevant experiences and instructive lessons in formulating and implementing business strategies. The case highlights the importance of contextual leadership intelligence and competence in enabling entrepreneurial business activities. Case overview/synopsis: Tomato Jos (Nigeria) is a large tomato processing business in Kaduna, Nigeria. Nigeria is the second-largest producer of tomatoes in Africa, with Egypt as the largest. The country ranks 14th overall as a world producer. In Africa, and specifically Nigeria, there is a strong push to support small-scale farmers as a source of employment creation, as well as meeting the needs of food security. The CEO, Mira Mehata, is an ex-pat graduate from the USA with strong Agri sector experience. The business has received extensive support from the Kaduna Government as the business has secondary objectives to assist small-scale farmers in the region. Farmers need consistent off takers and reasonable set prices to see a return on their investment and Tomato Jos plays that role of being the middle-man. This results in less wasted produce – the bane of farmers globally. The price for fresh tomatoes is about three times that of processed tomatoes IE in paste or sauce – so that is an added challenge for farmers to see the value in processed tomatoes. The business currently has a 2% Market Share in Nigeria with a target of 10% over the next five years. The business so far has invested three billion Naira and plans a further five billion Naira over the next few years. The business is seen as a high-profile success story with a supportive eco-system with a push from both the Nigerian Government and some major private sector players example Dangote. Complexity academic level: The case is intended for use in MBA and Executive education courses in Strategy, Marketing and Leadership. Supplementary materials: Teaching notes are available for educators only. Subject code: CCS 11: Strategy.